Astrometric Follow-up of Near-Earth Asteroid 2024 YR4 During a Torino Scale Level 3 Alert - Micheli, Marco; Devogèle, Maxime; Denneau, Larry; Ryan, Eileen V.; Ryan, William H.; Pravec, Petr; Hornoch, Kamil; Kučáková, Hana; Fatka, Petr; Brucker, Melissa J.; Lejoly, Cassandra; Moskovitz, Nicholas; et al. (Springer Science and Business Media LLC, 2026)
The discovery of 2024 YR4 presented the planetary defense community with the most significant impact threat in almost two decades, reaching level 3 on the Torino scale. The community, now mature and well-organized, responded with a global observational effort. Astrometric measurements, forming the basis for orbital refinement and impact prediction, were a central component of this response. In this paper, we present the astrometric data collected by the international community, from the time of discovery until the object became too faint for all existing observational assets, including JWST. We also discuss the coordination role played by the International Asteroid Warning Network, and the importance of publicly available image archives to enable precovery searches.